Keterkaitan Sikap dan Komitmen Profesional terhadap Niat Melakukan Whistleblowing - Siwi Ayu Kumala; Nur Laila Yuliani; Anissa Hakim Purwantini; Barkah Susanto (STIE PGRI Dewantara Jombang, 2025)
Corruption causes losses to both organizations and countries. Whistleblowing is an effective method to find corruption. This study aims to empirically test and analyze the influence of attitudes, behavioral control, religiosity and professional commitment on whistleblowing intentions. Regional Apparatus Organizations in Purworejo Regency are the samples in this study. Based on the purposive sampling technique, the research sample consisted of 86 respondents, namely State Civil Apparatus who hold the positions of Treasurer, Head of Finance Sub-Division, Head of Service/Agency, and Finance Staff with a minimum of one year of experience. Hypothesis testing uses multiple linear regression. The findings of this study found that there was a positive impact of attitudes and professional commitment on whistleblowing intentions. Meanwhile, behavioral control and religiosity did not affect whistleblowing intentions.